An Update on the Multifaceted Roles of STAT3 in the Heart - Harhous, Zeina; Booz, George W.; Ovize, Michel; Bidaux, Gabriel; Kurdi, Mazen (Frontiers in Cardiovascular Medicine, 2019)
Signal transducer and activator of transcription 3 (STAT3) is a signaling molecule and transcription factor that plays important protective roles in the heart. The protection mediated by STAT3 is attributed to its genomic actions as a transcription factor and other non-genomic roles targeting mitochondrial function and autophagy. As a transcription factor, STAT3 upregulates genes that are anti-oxidative, anti-apoptotic, and pro-angiogenic, but suppresses anti-inflammatory and anti-fibrotic genes. Its suppressive effects on gene expression are achieved through competing with other transcription factors or cofactors. STAT3 is also linked to the modification of mRNA expression profiles in cardiac cells by inhibiting or inducing miRNA. In addition to these genomic roles, STAT3 is suggested to function protectively in mitochondria, where it regulates ROS production, in part by regulating the activities of the electron transport chain complexes, although our recent evidence calls this role into question. Nonetheless, STAT3 is a key player known to be activated in the cardioprotective ischemic conditioning protocols. Through these varied roles, STAT3 participates in various mechanisms that contribute to cardioprotection against different heart pathologies, including myocardial infarction, hypertrophy, diabetic cardiomyopathy, and peripartum cardiomyopathy. Understanding how STAT3 is involved in the protective mechanisms against these different cardiac pathologies could lead to novel therapeutic strategies to treat them.